Optimalisasi Kinerja Karyawan Melalui Strategi Edukasi dan Pelatihan - Solehan Solehan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
Optimizing employee performance is the main goal in human resource management, and education and training strategies play a key role in achieving this goal. Employee education and training aims to improve abilities, knowledge and skills, thereby producing employees who are competent, innovative and adaptive to change. The process of implementing this strategy includes needs analysis, curriculum development, implementation and ongoing evaluation. The benefits obtained include increased skills and knowledge, higher productivity, adaptability to industry changes, and increased employee satisfaction and loyalty. Case studies from various industries show that companies that are committed to employee development through effective training programs are able to achieve significant results. Although there are challenges such as budget constraints and resistance to change, the right strategy can overcome these obstacles and encourage optimal employee performance. Employee education and training, therefore, is a worthwhile investment in the long-term success of an organization.